Prognostic value of the lactate dehydrogenase to albumin ratio in cancer patients - Chai, Dongqi; Yang, Tao; Zhang, Lilong; Hui, Yuanjian; Feng, Jiarui; Wang, Weixing (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to explore the prognostic relevance of the lactate dehydrogenase-to-albumin ratio (LAR) in cancer patients.MethodsA comprehensive literature search was conducted across PubMed, EMBASE, and the Cochrane Library for studies published before March 15, 2025. The primary outcomes included pooled hazard ratios (HRs) and corresponding 95% confidence intervals (CIs) for overall survival (OS), progression-free survival (PFS), and recurrence-free survival (RFS). In addition, a retrospective cohort of 71 hepatocellular carcinoma (HCC) patients treated with immune checkpoint inhibitors at our institution was analyzed to assess the prognostic impact of baseline LAR on OS and PFS.ResultsEighteen studies comprising 8,335 patients were incorporated into the meta-analysis. Elevated LAR was consistently associated with poorer outcomes: OS (HR: 2.02, 95% CI: 1.74–2.34, p < 0.001), PFS (HR = 1.35, 95% CI: 1.14–1.61, p < 0.001), and RFS (HR = 1.97, 95% CI: 1.47–2.64, p < 0.001). Subgroup evaluations stratified by LAR thresholds, geographical regions, treatment regimens, and statistical models confirmed the robustness of these associations. In our institutional cohort, patients presenting with pretreatment higher LAR experienced significantly diminished OS (HR = 2.04, 95% CI: 1.19–3.57, p = 0.008) and PFS (HR = 1.89, 95% CI: 1.14–3.13, p = 0.01) compared with those having lower LAR levels.ConclusionThese findings underscore the prognostic value of pretreatment LAR in cancer patients. Integrating LAR into clinical decision-making may aid clinicians in enhancing risk stratification and personalizing treatment strategies.